Integration of Da'wah-Based Curriculum to Build Progressive Spirituality and Character in Indonesian Islamic Education - Syamsu T; A Rizal (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study investigates the role of da'wah in enhancing spirituality as a foundation for developing progressive character traits—such as integrity, responsibility, and social awareness—within the community of Sidenreng Rappang Regency, South Sulawesi. It explores how spiritual development through Islamic preaching can lead to positive individual and collective transformation. A qualitative approach was employed, utilizing interviews, field observations, and literature reviews to gather data on local da'wah practices and their impact on community values. Key informants included religious leaders, community members, and local officials involved in spiritual and social initiatives. Findings reveal that effective da'wah activities significantly contribute to increased personal spirituality and community cohesion. Approximately 80% of participants reported noticeable positive changes in attitudes and behaviors following sustained engagement with da'wah-based programs. These changes included stronger ethical awareness, enhanced social responsibility, and a greater sense of communal harmony. The results suggest that da'wah serves not only as a religious practice but also as a transformative social instrument. By embedding Islamic values into everyday life, da'wah fosters a spiritual environment that supports the formation of progressive character traits. This underscores its strategic role in building a socially conscious and morally grounded society in Sidenreng Rappang. Da'wah plays a critical role in spiritual and character development, making it an essential element in promoting holistic societal progress.